Risk sharing with the monarch: Contingent debt and excusable defaults in the age of Philip II, 1556-1598 - Mauricio Drelichman; Hans-Joachim Voth (University of Zurich, Department of Economics, 2014)
Contingent sovereign debt can create important welfare gains. Nonetheless, there is almost no issuance today. Using hand-collected archival data, we examine the first known case of large-scale use of state-contingent sovereign debt in history. Philip II of Spain entered into hundreds of contracts whose value and due date depended on verifiable, exogenous events such as the arrival of silver fleets. We show that this allowed for effective risk-sharing between the king and his bankers. The existence of statecontingent debt also sheds light on the nature of defaults - they were simply contingencies over which Crown and bankers had not contracted previously.
Keywords: H1; H63; N43; 330; Sovereign debt; contingent debt; fiscal policy; debt crisis